CRISIS AS A FORM OF MANIFESTATION OF FINANCIAL INSTABILITY: ESSENCE AND CONSEQUENCES FOR LOCAL ECONOMIC DEVELOPMENT (Economic journal of Lesya Ukrainka Volyn National University, 2023)
The war in Ukraine, the consequences of the pandemic, and record inflation provoked an unprecedented economic, social and humanitarian crisis, which in turn increased financial instability and reduced the stability of socio-economic systems at various levels. Newly formed communities faced a new reality and challenges for further progress, which indicates the inevitability of a new large-scale economic crisis. In this sense, the issues of leveling the manifestations of the crisis, working out mechanisms to minimize its negative consequences or taking preventive or corrective measures to ensure the financial stability of territorial communities were brought up to date.The purpose of the article is to reveal the essence of crisis phenomena and financial instability, to substantiate the peculiarities of their manifestation at the local level.In the article, a retrospective analysis of research on crisis phenomena is carried out, the essence of the crisis and related concepts such as "economic and financial crisis" is revealed, their interrelationship and interdependence are argued. The causes of crises are singled out. The problematic aspects of the crisis caused by the pandemic and the war are emphasized. The consequences of the crisis for local economic development are determined. It is shown that dynamic changes in all spheres of life of territorial communities require immediate appropriate strategic and tactical decisions. It was emphasized that the crisis situation that has developed in Ukraine and communities is extremely difficult, unpredictable and difficult to manage, it is timely to develop approaches, measures, tools to improve the directions of the formation and implementation of financial policy and the development of anti-crisis tools for local economic development. Alleviation of financial instability cannot be achieved by budgetary/monetary or fiscal policy measures or instruments alone, their coordination and coherence is required.
Keywords: financial instability, crisis, local economic development, territorial communities, war, pandemic